COMM3 - Verderber, Kathleen S. 1949-; Sellnow, Deanna D.; Verderber, Rudolph F. (Cengage Learning, 2015)
Created by the continuous feedback of a "student-tested, faculty-approved" process, this book delivers a visually appealing, succinct print component, tear-out review cards for students and instructors and a consistent online offering with CourseMate.